Telemedicine and AI in Occupational Skin Disease Management: A Contemporary Review - Purwoko, Reza Yuridian; Muliadi, Jemie; Roestam, Rusdianto; Wan Sen, Tjong Wan Sen; Pamungkas, Lukas Sangka; Nugroho, Anto Satriyo; Armi, Nasrullah; Supriyadi, Muhamad Rodhi; Melati, Rima; Alfaqih, Muhammad Subhan; Montolalu, Ivan Adrian; Ruhdiat, Rudi; Ferianasari, Inneke Winda; Aryanti, Evy Aryanti; Saputra, Silvan; Asmail, Asmail; Rahayaan, Manuela; Hi Rauf, Siti Nuraini (FIRM Journal of Management Studies, 2023)
Occupational skin diseases present significant challenges to workplace health, impacting both productivity and quality of life. The integration of telemedicine and artificial intelligence (AI) has transformed dermatological care by facilitating remote consultations, enabling early diagnosis, and supporting continuous monitoring. The COVID-19 pandemic has accelerated the adoption of digital health solutions, underscoring their potential to enhance accessibility and efficiency in occupational dermatology.AI-driven innovations, including machine learning algorithms and wearable technologies, have further improved diagnostic accuracy and patient management. However, challenges such as healthcare disparities, technological limitations, and workplace-specific factors continue to hinder widespread implementation. This review explores the evolving role of telemedicine and AI in managing occupational skin diseases, highlighting key challenges, emerging opportunities, and policy considerations for enhancing workplace health outcomes.